När och varför dör smågrisarna under diperioden? - Wik, Ellen (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2015)
The purpose of this study was to compile when and why piglets die during the suckling peri-od. Piglet mortality is an important factor influencing the profitability of piglet production. There are many factors that play a role and interact whit each other. This study summarizes when the piglets die during the suckling period and reasons why the piglets die. The infor-mation given is crushed, illness, management/environmental, genetic influence and piglet birth weight/farrowingprocess. The conclusion of this study is that many pigs die in early lac-tation due to crushing and starvation which shows that it is important that the piglets are born strong, can avoid getting crushed and compete for the milk. This makes it important that a good environment is provided to the piglet and that the piglets get the care they need. Genetic effects vary greatly in results between different studies but most studies show that it is possi-ble to improve piglet survival with breeding.